Intellectual Property Rights in Franchise Agreements According to Indonesian Positive Law - Pujangga, I Kadek Sabda; Sarjana, I Made (University of Udayana, 2025)
This research examines the position of Franchise Agreements according to Indonesian Positive Laws and the protection of Intellectual Property Rights in Franchise Agreements in Indonesia. The methodology applied is a normative approach, analyzing the function of franchise agreements within the Indonesian positive legal framework as well as the protection of IPR through contextual and regulatory perspectives (insert approach). The analysis results reveal that based on PP Number 35/2007 concerning Franchising, franchisees are required to report the franchise agreement to the government after signing. Comprehensive legal protection for IPR in the franchise system is regulated by various legal instruments, including the Trade Secrets Law, Copyright Law, Patent Law and Trademark Law.